Socioecological dynamics and resilience of ornamental fishing in Barcelos, Rio Negro, Amazonas, Brazil - Sobreiro, Thaissa (Sustainability in Debate, 2016)
We characterize the dynamics of ornamental fishing in the municipality of Barcelos (Brazilian Amazon) from the perspective of socio-ecological systems and resilience theory. Using the adaptive cycle as a heuristic model, we present the social actors involved in the activity, its history and some factors related to its collapse is suggested. Although ornamental fishing might be ecologically and socially viable, economic factors contributed greatly to its decline. The traditional use of multiple natural resources, cash transfer programs and income opportunities from the commercial and sport fishing, are factors that are contributing to the reorganization of the system. The effects of these changes are not known yet, but an increase in fishing pressure on stocks can adversely affect the resilience of the ecological system.